Prevalence of Posttraumatic Stress Disorder (PTSD) among the Iraqi Repatriated Prisoners of the Iran-Iraq War, 1980-1988 - Al-Ameri, maan; gee, Ivan; Ma'ala, iqbal; Wallymahmed, Akhtar (Iraqi National Journal of Nursing Specialties, 2015)
Objective: To determine the prevalence of Posttraumatic Stress Disorder (PTSD) among Iraqi repatriatedprisoners of Iran-Iraq war, and the relationship with demographic factors.Methodology: A descriptive study was carried out from Oct. 18th, 2009 through Jan. 10th, 2010. A nonprobabilitybased snowball sampling technique was used to recruit 92 Iraqi repatriated prisoners of war(IRPOWs) who had visited Ministry of Human Rights. A data collection instrument was constructed thatconsisted of six demographic characteristics, and eight items to measure the level of PTSD in POWs. Data werecollected with the constructed instrument during a brief interview. Data were analyzed through the application ofdescriptive statistical analysis: percentages; frequencies and inferential statistic analysis (Pearson correlationcoefficient).Results: The study revealed that the majority of IRPOWs have some level of PTSD (78.3%). Proportions ofIRPOWs with low, medium and high severity PTSD: Low (29.3%); medium (32.6%) and high (16.4%).Statistically significant relationships were observed between PTSD and duration of captivity, marital status andlevel of education.Recommendations: The study recommends special mental health services centres are established withinprimary health care centres in order to diagnose and treat them and that further studies are conducted to exploreeffective treatments for IRPOWs